Criticisms The Government's Role of Zakat Regulation in Indonesia for Improving the Zakat Potential - Mu’adzah, Nadiyah; Rachmad, Dedy (Islamic Social Finance, 2024)
This research was conducted to determine previous research trends regarding zakat regulation as well as the sentiment from these studies regarding the policy and implementation of zakat regulations in Indonesia. The methodology used in this research is a qualitative method with descriptive statistics on secondary data from 151 literature studies related to zakat regulation published and available on Dimensions.ai over a period of 7 years (2017-2023). The data analysis techniques used are meta-analysis and sentiment analysis which are processed using Microsoft Excel 2019 and SentiStrength software. Then, to reveal this problem in depth and comprehensively, a Systematic Literature Review (SLR) study was also carried out. The research results show that the publication of scientific literature regarding zakat regulation in Indonesia continues to increase every year, indicating that this field is quite interesting to discuss for researchers and has extensive research space and continues to develop. This study can be used as a reference in identifying influential authors, articles and journals so that future researchers will find it easier to find references that have a big influence on the development of literature on zakat regulation in Indonesia. Apart from that, by knowing what things were criticized from the negative perceptions of previous researchers regarding the policy and practical application of zakat regulation in Indonesia, it is hoped that this research can become evaluation material for regulators and policy makers to revitalize existing regulations to realize their potential.